Evaluation of Renal Toxicity of Colistin Therapy With Neutrophil Gelatinase-associated Lipocalin: a Biomarker of Renal Tubular Damage (Iranian Journal of Kidney Diseases, 2017)
Introduction. Nephrotoxicity has been a concern with new dosing regimens of colistin. This study was designed to compare nephrotoxicity of high dose and conventional dose of colistin and the ability of detecting it using neutrophil gelatinase-associated lipocalin (NGAL). Materials and Methods. A randomized clinical trial was carried out on 40 patients with multidrug-resistant gram-negative infections assigned into 2 groups to receive high and conventional doses of colistin. Blood samples were taken 4 times for measuring serum NGAL. The incidence of acute kidney injury was also evaluated based on the risk, injury, failure, loss, end-stage renal disease (RIFLE) criteria. Results. Baseline levels of NGAL were not significantly different between the patients on the high dose and conventional dose of colistin. The mean NGAL levels on day 10 were 762.14 ± 415.44 pg/mL and 623.67 ± 272.61 pg/mL, respectively.  However, between-group analysis did not show a significant difference in the NGAL levels. The prevalence of acute kidney injury was 60% and 15% based on the RIFLE criteria, in the high-dose and conventional-dose groups, respectively (P = .003). Conclusions. Although colistin-induced nephrotoxicity was not confirmed with NGAL levels, our findings, however, showed a higher incidence of acute kidney injury associated with high-dose colistin, defined by the RIFLE criteria. Higher levels of NGAL in the acute kidney injury patients were associated with high-dose regimen of colistin.